Ficus plants: State of the art from a phytochemical, pharmacological, and toxicological perspective. (7th October 2020) - Salehi, Bahare; Prakash Mishra, Abhay; Nigam, Manisha; Karazhan, Natallia; Shukla, Ila; Kiełtyka‐Dadasiewicz, Anna; Sawicka, Barbara; Głowacka, Aleksandra; Abu‐Darwish, Mohammad Sanad; Hussein Tarawneh, Amer; Gadetskaya, Anastassiya V.; Cabral, Célia; et al.
Abstract : Ficus genus is typically tropical plants and is among the earliest fruit trees cultivated by humans. Ficus carica L. is the common fig, Ficus benjamina L. is the weeping fig, and Ficus pumila L. is the creeping fig. These species are commonly used in traditional medicine for a wide range of diseases and contain rich secondary metabolites that have shown diverse applications. This comprehensive review describes for Ficus genus the phytochemical compounds, traditional uses and contemporary pharmacological activities such as antioxidant, cytotoxic, antimicrobial, anti‐inflammatory, antidiabetic, antiulcer, and anticonvulsant. An extended survey of the current literature (Science Direct, Scopus, PubMed) has been carried out as part of the current work. The trends in the phytochemistry, pharmacological mechanisms and activities of Ficus genus are overviewed in this manuscript: antimicrobial, antidiabetic, anti‐inflammatory and analgesic activity, antiseizure and anti‐Parkinson's diseases, cytotoxic and antioxidant. Health‐promoting effects, recent human clinical studies, safety and adverse effects of Ficus plants also are covered. The medical potential and long‐term pharmacotherapeutic use of the genus Ficus along with no serious reported adverse events, suggests that it can be considered as being safe.